2018
DOI: 10.1088/1361-6528/aaa2e8
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electronic and optical properties of arsenene/C3N van der Waals heterostructure by vertical strain and external electric field

Abstract: Searching for new van der Waals (vdW) heterostructure with novel electronic and optical properties is of great interest and importance for the next generation of devices. By using first-principles calculations, we show that the electronic and optical properties of the arsenene/CN vdW heterostructure can be effectively modulated by applying vertical strain and external electric field. Our results suggest that this heterostructure has an intrinsic type-II band alignment with an indirect bandgap of 0.16 eV, facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 55 publications
5
48
1
Order By: Relevance
“…The charge transfer of the GeP/Gr heterostructure, in fact, is determined by the competition between the influence given by vertical distance and the contact area, for example, 3% strain induces largest electron accumulation for the GeP layer among all strains. Hence, the charge transfer shown here is different from the case of C 3 N/arsenene heterostructure with monotonous variation by using vertical strain 55…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…The charge transfer of the GeP/Gr heterostructure, in fact, is determined by the competition between the influence given by vertical distance and the contact area, for example, 3% strain induces largest electron accumulation for the GeP layer among all strains. Hence, the charge transfer shown here is different from the case of C 3 N/arsenene heterostructure with monotonous variation by using vertical strain 55…”
Section: Resultscontrasting
confidence: 63%
“…It has been shown that the application of an external electric field ( E ext ) can effectively modulate the electronic properties of 2D heterostructure. More recently, some computational works have unveiled that the Schottky barrier heights of electron (normalΦnSB) and hole (normalΦpSB) can be tuned by the electric field 45,55. We thus consider that a tunable Schottky barrier heights for both electron (normalΦnSB) and hole (normalΦpSB) can be achieved for the GeP/Gr heterostructure via this route.…”
Section: Resultsmentioning
confidence: 98%
“…Evaluating the electronic properties of nanostructure semiconductors is crucial for improving their efficiency in electronics. Of these, applying mechanical strain and external electric fields have a long history in adjusting the electronic properties of semiconductors [23][24][25][26][27]. Researchers have found that nanostructures preserve their structure under tension, very higher and lower than their bulk lattice constants, which unbelievably improves their intrinsic performance in nanotechnology industries [28].…”
Section: Introductionmentioning
confidence: 99%
“…All the calculations are accomplished in CASTEP code. These tasks are based on periodic density functional theory (DFT) with the plane‐wave pseudopotential method . As for the energy band structures of the Ge/AlN HTS under E ‐field, the calculations are conducted in the DMoL3 code.…”
Section: Computational Model and Methodsmentioning
confidence: 99%